"V imenu objektivnosti" - Udovič, Boštjan (Javnost (Ljubljana), 2011)
The article analyses how Slovenian media reported on commercial diplomacy from January to June, 2011. The authors present the main features of media reporting on the subject, such as the presence of commercial diplomacy in the media, key journalistic sources, and the attitudes of dominant journalistic sources and media to commercial diplomacy. Commercial diplomacy is not the main subject of public debate in Slovenian media; reporting on the subject represents only 2.3% of the total number of items on foreign policy. Key journalistic sources debating the commercial policy pertain to political elites, in particular the representatives of the Ministry of Foreign Aff airs, who happen to be also its core actors. Sources representing economic interests are increasingly less present in the media; their attitudes towards commercial diplomacy, however, are equally positive, with the Chamber of Commerce as the only exception. In most cases, media reports on commercial diplomacy are indigent, event-related, and without additional commentary, whereas actors involved in commercial diplomacy usually tend to take a positive stance towards it.
Keywords: Slovenia; Slovenija; mass media; množični mediji; novinarstvo; journalism; diplomacija; diplomacy; zunanja politika; mednarodno poslovanje; mednarodni ekonomski odnosi